Are Ureaplasma spp. a cause of nongonococcal urethritis? A systematic review and meta-analysis. - Nan Zhang; Rong Wang; Xue Li; Xu Liu; Zhaobing Tang; Yunde Liu (PLoS ONE, 2014)
Background Nongonococcal urethritis (NGU) is the most common male reproductive tract syndrome. Ureaplasmas spp. including U. urealyticum and U. parvum, have been increasingly reported to be implicated in NGU. However, there are still many contradictions about their pathogenic role in NGU. Aims The goals of this study were to evaluate the association of Ureaplasmas spp. with NGU, and to compare the prevalence of Ureaplasmas spp. infection in China relative to the world average. Methods A systematic review and meta-analysis was conducted following standard guidelines for meta-analysis. The quality of included studies was assessed by Newcastle-Ottawa scale. Results A total of seven studies involving 1,507 NGU patients and 1,223 controls were eligible for meta-analysis. There was no significant difference in the Ureaplasma spp. positive rate between the NGU and control groups. However, the U. urealyticum positive rate was significantly higher in NGU patients compared to controls; the U. parvum positive rate was significantly higher in controls compared to NGU patients. Furthermore, within the NGU patient group, the positive rate of U. urealyticum was significantly higher than that of U. parvum, whereas within the control group, the opposite trend was observed. Compared to the world average, a significantly higher positive rate of Ureaplasma spp. was observed in both the NGU and control groups in China. Conclusions Our analysis supports that U. urealyticum, but not U. parvum, is an etiological agent in NGU. More detailed studies of these two species in China and the world could contribute to a better understanding of the epidemiology and pathogenesis, and facilitate the development of better strategies for treatment and prevention of NGU.